Participatory Approach in Designing Tunas Bangsa 02 PAUD School Learning Facilities - Tutut Nani Prihatmi; Ghoustanjiwani Adiputra; Hani Zulfia Zahro (Indonesia Emerging Literacy Education, 2022)
School’s learning facility is one of the crucial components in supporting optimal education to achieve the educational goals, including early childhood education (PAUD). However, Tunas Bangsa 02 PAUD School is a private school that raises its finances and does not take any school fees (free tuition). The improvements to infrastructure and teaching resources are limited and carried out independently. It is necessary to have proper and directed planning so that the development of the learning facility follows the most critical needs. This study describes the design of participatory assistance to map the learning facilities. The participants in this program were the owner of the foundation, financial donors, representatives of parents, and all teachers, accompanied by a team of experts. Of the eight participatory design processes that have been implemented in this initial study, the researchers found that the participatory approach can be applied optimally and able to provide convenience for the school to map, plan and arrange their learning facilities, and a program design of Consultation Stage that consists of 5 stages can be implemented in the following years.